Intergenerational transmission of parental neuroticism to emotional problems in 8‐year‐old children: Genetic and environmental influences. Issue 4 (30th November 2021) - Ask, Helga; Eilertsen, Espen M.; Gjerde, Line C.; Hannigan, Laurie J.; Gustavson, Kristin; Havdahl, Alexandra; Cheesman, Rosa; McAdams, Tom A.; Hettema, John M.; Reichborn‐Kjennerud, Ted; Torvik, Fartein A.; Ystrom, Eivind
Abstract: Background: Children of parents with high levels of neuroticism tend to have high neuroticism themselves as well as increased risk of experiencing symptoms of anxiety and depression. It is not yet clear how much of this link is attributable to a potential effect of parent on child (e.g., via a socializing effect) versus to shared genetic risk. We aimed to determine whether there is an intergenerational association after accounting for genetic transmission and assortative mating. Methods: We used data from the Norwegian Mother, Father and Child Cohort Study including 11, 088 sibling pairs in the parental generation, their partners ( N = 22, 176) and their offspring ( N = 26, 091). Exposures were maternal and paternal neuroticism (self‐reported), and the outcomes were neuroticism, symptoms of depression, and symptoms of anxiety in 8‐year‐old children (mother‐reported). Results: After accounting for assortative mating in parents (phenotypic r = 0.26) and genetic transmission (explaining 0%–18% of the mother‐offspring correlations), potential maternal effects explained 80% (95% CI = 47–95) of the association with offspring neuroticism (mother‐child r = 0.31), 78% (95% CI = 66–89) of the association with offspring depressive symptoms ( r = 0.31), and 98% (95% CI = 45–112) of the association with offspring anxiety symptoms ( r = 0.16). Intergenerational transmission of genetic variants associated with paternal neuroticism accounted for ∼40% (CI = 22%–58%) of the father‐offspring correlations with neuroticism and symptoms of depression ( r = 0.13 and 0.13, respectively) but none with offspring symptoms of anxiety ( r = 0.05). The remaining father‐offspring correlations were explained by maternal influences through assortative mating. Conclusions: These results are consistent with direct effects between maternal and offspring neuroticism and between maternal neuroticism and offspring symptoms of anxiety and depression. Further understanding of these intergenerational processes will require an adequate model of how these constructs (neuroticism, anxiety and depression) relate to each other within generations. Abstract :